Effects of microbial phytase supplementation on feed consumption and egg production of laying hens - Ciftci, Mehmet; Dalkilic, Bestami; Azman, M. Ali (Asian Network for Scientific Information, 2005)
In this study, the effects of microbial phytase supplementation in diets were investigated on feed intake, egg production and feed efficiency in laying hens. The experiment was carried out between the July 15th to October 15th. 120 Nick Chick White hens at 210 days of age were divided into four groups of 40 each. Each cage contained 5 hens. Treatment groups were fed the basal diet (Control Group) or the basal diet supplemented with 300 U/kg of microbial phytase (Group A) and 600 U/kg of microbial phytase (Group B). Birds in each group were fed a balanced diet ad libitum. Daily feed intake, feed efficiency, egg production and egg weight differed between treatment groups (P<0.01). However initial and final body weights were similar in all groups. It can be concluded that supplementation of microbial phytase to diets improved hen productivity. © Asian Network for Scientific Information, 2005.
Keywords: Egg; Feed intake; Laying hen; Microbial phytase